Intelligent matching method of vehicle navigation map information based on vehicle networking technology. (5th August 2019) - Le, Qun; Jiang, Kun; Zhang, Feng
In order to improve the intelligent matching of vehicle navigation map information, an intelligent matching method of vehicle navigation map information based on vehicle networking technology is proposed to construct an intelligent matching and information scheduling algorithm of vehicle navigation map information in vehicle networking, based on information fusion and correlation matched filtering detection and a data transmission channel model for intelligent matching of vehicle navigation map information in vehicle networking, and analyse the multi-path characteristics of vehicle navigation map information transmission channel. The simulation results show that the proposed algorithm has better intelligence in vehicle navigation map information matching, better channel equalisation and better adaptive performance in vehicle networking communication.